The Mediterranean diet and lifestyle - Garcia Hernandez, Silvia; Montserrat Mesquida, Margalida; Antoni Tur, Josep; Bouzas, Cristina (Archives of Pharmacy, 2023)
The Mediterranean Diet (MedDiet) is characterized by a high intake of fruit, vegetables, whole grains, legumes, and olive oil, moderate consumption of poultry and fish, and a limited intake of red meat and minimal processed foods. It has been associated with many health benefits, including the prevention and management of metabolic syndrome, diabetes, cardiovascular disease, neurodegenerative diseases, and certain types of cancer, as well as increased longevity and reduced risk of mortality. The protective effects of the MedDiet are related to its antioxidant and anti-inflammatory properties. The MedDiet is not only a health-promoting dietary pattern, but it is also environmentally sustainable, showing a negative correlation with greenhouse gas emissions, among other environmental indicators. In addition to the MedDiet, the Mediterranean lifestyle, which involves regular physical activity, adequate rest, and socializing during meals, has also been linked to beneficial health outcomes. Preventive strategies for noncommunicable diseases should focus on promoting the Mediterranean lifestyle and implementing early detection and prevention programs, at both individual and social levels.